Aplicação de percolado de aterro sanitário no cultivo de girassol no semiárido brasileiro - Coelho, Daniela da Costa Leite (Universidade Federal Rural do Semi-Árido, 2016)
The leachate from landfills is a highly impactful liquid waste to the environment, making it essential to conducting research that provide a better and more precise characterization of the leachate produced in the cells of the landfill, considering the behavior of their constituents through soil, surface water and subterranean plants and, especially aimed at new techniques for treatment and disposal of the liquid waste in the environment. In this context, it objectified with the work, analyze the effect of the application of landfill leachate (PATS), through drip irrigation system, soil quality and sunflower crops (Helianthus annuus L.) in the Brazilian semiarid region. For accomplishment of this work, it was mounted an experimental area at the Universidade Federal Rural do Semi-Árido – UFERSA, Campus Mossoró. Each experimental bit was built in the dimensions of 2.0 x 5.0 m, and spacing of 2.0 m between blocks and 1.0 m between plots of the same block, where was cultivated the sunflower, cultivar BRS 324, in soil classified as argisoil red-yellow eutrophic. They treatments were: T1 – 100 % water (control); T2 – 80 % water and 20% PATS; T3 – 60 % water and 40 % of PATS; T4 – 40 % water and 60% PATS; and T5 – 20 % water and 80 % of PATS. During the experimental period, they were analyzed in parallel the chemical characteristics of soil and crop productivity, the physicochemical characteristics of the leachate and the supply mains water, and the performance of drip irrigation units. It adopted the delineation in blocks randomized with five treatments (T1, T2, T3, T4 and T5) and four repetitions, and to perform the statistical analysis was used statistical computer program Sisvar 5.6. The results indicated that only CEes , P, Fe and Zn suffered significant effects of different dosages PATS applied in interaction with the application time and for the two depths analyzed. The concentrations of N, Ca, Mg, Fe and Cd decreased considerably during the time of sampling. The levels of pH, CEes, N, P, Na, Ca, M.O., SB, CTC, T, V, PST, Mn, Zn and Pb decreased over the soil profile, and Fe increased. The concentrations of Cu, Ni and Cd were practically constant, the K and Mg did not show a pattern of variation, and Al3+, H + Al and m were null. In relation to culture, it showed that the variables AP, NF, DCaule, DCapítulo, weight of seeds, P, Na, Mg, Fe, Mn, Zn and Pb showed statistically significant differences between the treatments. Analyzing the changes in drip irrigation system performance caused by the application of leachate from landfills, it was found that there was a partial clogging of drippers where the fact that the setting time and amount of irrigation through valves alter the pressure service, decreasing the deposition of sediments and biofilm formation within the drippers lines. The treatment showed better results with respect to vegetative characteristics, production and sunflower plant tissue composition was the treatment T3 (water requirement of the crop with 60 % of AA and 40 % of PATS), and that high concentrations of PATS applied to the soil cause a reduction in quality and hence decrease in biomass of this culture and/or high concentrations in the plant tissue
Application of landfill leachate in sunflower cultivation in the Brazilian semiarid region
Keywords: Sustentabilidade; Resíduo líquido urbano; Reuso; Oleaginosa; Biomassa; Sustainability; Urban liquid waste; Reuse; Oleaginous; Biomass; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO